دراسة فعالية تنقية المياه المستعممة باستخدام مرشح مزروع بنبات - الوصيف الزهرة; لعيس هاجر; قحف إيمان (جامعة الشهيد حمه لخضر بالوادي, 2025)
تعد معالجة المياه المستعممة حلاً فعالًً لإعادة استخداميا في الفلاحة أو الصناعة، بدلًً مف التخمص منيا بطرؽ مكمفة. تناولت الد ا رسة طريقة بيولوجية باستخدا نبات Ipomoea pes caprae subsp ، حيث أُنشئ نظا مكوّف مف ثلاثة أحواض مختمفة الظروؼ. أظير الحوض الذي زُرع فيو النبات فعالية كبيرة في تحسيف نوعية المياه مف خلاؿ تقميؿ المواد العضوية والصمبة بنسبة ممحوظة، إذ ت تسجيؿ:  انخفاض في DBO5 بنسبة 48.18 % .  انخفاض في MES بنسبة 97.56 % .  انخفاض في DCO بنسبة 84.56 % .  زيادة في الأوكسجيف الذائب بنسبة 3.21 ممغ/لتر.  انخفاض في الدليؿ الييدروجيني إلى 91.28 % Wastewater treatment is an effective solution for its reuse in agriculture or industry, instead of disposing of it through costly methods. This study explored a biological method using the plant Ipomoea pes- caprae subsp., where a system composed of three basins under different conditions was established. The basin planted with the plant showed significant effectiveness in improving water quality by noticeably reducing organic and solid matter. The recorded results were as follows:  Reduction in DBO5 by 48.18 %  Reduction in TSS by 97.56 %  Reduction in DCO by 84.56 %  Increase in dissolved oxygen by 3.21 mg/L  Decrease in pH indicator to 91.28%
Ipomoea pes caprae subsp Etude des performances épuratoires du traitement des eaux usées par un filtre planté de Ipomoea pes-caprae subsp
مذكرات ماستر تخصص هندسة كيميائية
Keywords: المياه المستعممة، Ipomoea pes caprae subsp ، المواد العضوية.; Wastewater; Ipomoea pes- caprae subsp.; organic matter